FENOMENA ISBAL DAN MEMANJANGKAN JENGGOT: ANALISA SOSIAL HISTORIS HADIS NABI MUHAMMAD - Muhammad Yusron; Muhammad Alfatih Suryadilaga (IAIN Surakarta, 2018)
This research is based on the phenomenon of people with thick beards and anti- isbal (cloth under the ankles) has become a unique character in various layers of Muslims. The pressing point of prohibiting the imposition of cloth under the ankle is the existence of the arrogance of the person wearing it, so it can be assumed that what should be avoided is the arrogant nature itself, not the imposition of cloth in specific. Meanwhile, the command to keep the beard accompanied by orders to cut the mustache is associated as a distinguishing form with the Majus people in the Classical era. However, considering its temporal nature, which means it is possible to change and by the situation and conditions. For the time being, Muslim identity is certainly not just by relying on beards, especially in situations where beards have become a trend of the appearance of anyone and anywhere.